Dental health in the shadows of global commitments: Addressing neglected priorities in lower middle-income countries - Wajiha Qamar (Journal of the Pakistan Medical Association)
I am writing to draw your attention to a serious concern that requires our attention around global health commitments: the frequently disregarded and undervalued dental reforms. In the realm of global health commitments, dental reforms are often ignored and underestimated. (1) Despite significant advancements in many other facets of health owing to these commitments, dental health remains marginalized within its sphere creating a glaring disparity, especially in lower middle-income countries where it’s a crucial concern.(2)